The Influence of State Defense Training and Motivation on The Performance of The Civil Apparatus in The Tni Spers - Suharno Pawirosumarto; Antonius Setyadi; Sunda Ariana; Yunata Kandias Akbar (Dinasti Publisher, 2023)
Aims - This study aims to determine the effect of State Defense training and motivation on Employee Performance in State Civil Apparatus (ASN) at Indonesian National Armed Forces (TNI) Headquarters Personnel Staff. Design/methodology/approach - The study population were employees at SPERS TNI, where 71 samples were determined through the Slovin formula, by using a proportional random sampling technique. A total of 71 distributed questionnaires were also returned appropriately, accompanied by data processing and analysis performances. In addition, descriptive statistics and multiple linear regression analysis methods were used with SPSS 22 software. Result – The results showed that training and motivation positively and significantly affected performance. For simultaneous measurements, both variables also influenced performance positively and significantly. Originality/Value – Based on the results, the role of developing TNI personnel was one of the functions of the Organizational Staff. This emphasized the development of both TNI and ASN personnel capabilities, through increased education, training, and motivation. Therefore, performance is unachievable without elevated competence and motivation.